Tamil : a biography - Shulman, David Dean, 1949- (London : The Belknap Press of Harvard University Press, 2016)
This book explores two millennia of south Indian Tamil civilization, with a special emphasis on the way Tamil speakers and literati understood the unique features of their language and the major cultural themes articulated in Tamil over this long time span. Tamil is one of the great world languages, with its 80 million speakers, its ancient, classical past, and the profound richness of its cultural traditions, which spread throughout South Asia and beyond to Sri Lanka and Southeast Asia and, today, to a large Tamil Diaspora scattered around the globe. Presented in the format of a south Indian musical composition, the chapters take the reader through the whole of Tamil cultural history, from its beginnings at the end of the first millennium B.C. through the stunning poems of love and war known as "Sangam Poetry", the burst of intense religious movements in the mid-first-millennium A.D., the Chola period of imperial expansion, and into late-medieval and modern times, including present-day Tamil politics and the vast cultural production of Chennai, Madurai, and Tanjavur. The treasures of the Tamil language deserve a wide audience--thus the book is aimed at readers with no special knowledge of India no less than at speakers and connoisseurs of Tamil. Translated verses and spicy stories of poets, lovers, musicians, warriors and kings fill the pages of this book, which paints a wide-angle, panoramic canvas of one of the most creative civilizations in the history of South Asia as it evolved and transformed itself from the distant past up to our own generation.--
Beginnings: alapanam -- First budding, Tamil from the inside : pallavi -- Second budding, the musical self : anupallavi -- The imperial moment, truth, and sound : caranam 1 -- Republic of syllables : caranam 2 -- A Tamil modernity : caranam 3 -- Beyond the merely modern : ragamalika
Includes bibliographical references (pages 357-383) and index
Keywords: Tamil (Indic people) -- Intellectual life; Tamil (Indic people) -- History; Tamil language -- History; Tamil literature -- History and criticism; Tamil poetry -- History and criticism; India -- Civilization